THE PEDESTRIAN MOVEMENT ANALYSIS (Perner's Contacts, 2006)
The kinematical values (distance, time, velocity, acceleration) characterised pedestrian movement are important input data for the next accident reconstruction. When we try to model the pedestrian movement, it is applicable to know the real measured values of walking (velocity and acceleration of different pedestrian categories). Creating of the database (course of velocity and acceleration in dependence on distance) for different pedestrian categories was the reason to elaborate at the Institute of Forensic Engineering in Zilina the work named: The pedestrian movement analysis. The paper shows the methodology and brief conclusions of the work.